Condições de atmosfera controlada, temperatura e umidade relativa no armazenamento de maçãs 'Fuji' - Brackmann, Auri (2005)
This experiment was carried out with the objective to evaluate the effect of temperature, relative humidity (RH) levels and O2 partial pressures on the quality of 'Fuji' apples stored on controlled atmosphere (CA). The experimental design was entirely randomized with four replications of 25 fruits. Evaluated treatments were: storage at 0.5ºC under CA with (1) 0.7kPa O2 and (2) 1.0kPa O2; storage at 0.5ºC under CA with (3) 0.7kPa O2; (4) 1.0kPa O2; (5) 1.0kPa O2 plus low RH 90%; (6) 1.0kPa O2 after 2 days at 20ºC (delayed storage) and (7) 1.0kPa O2 after 1 month of cold storage. Partial pressures CO2 were maintained lower than 0.5kPa in all treatments. In general, storage conditions evaluated in this work did not allow significative differences on quality maintenance of 'Fuji' apples after 8 months of storage plus 7 days of shelf-life. However delayed storage, through the placing of fruits at 20ºC during 2 days before transfer to CA with 1.0kPa O2 +<0.5kPa CO2 at -0.5ºC, and cold storage of fruits during 1 month before CA storage, exhibited good results on rot control after 7 days of shelf-life at 20ºC, especially when compared with storage at 0.5ºC under CA with 0.7 and 1.0kPa O2 +<0.5kPa CO2.